Kegiatan Keagamaan Solusi Penanggulangan Degradasi Moral - Fatikah , Noor; Lailatur Rohmah, Alif (ILJ: Islamic Learning Journal, 2025)
This article is motivated by the phenomenon of moral degradation among Generation Z students, such as the use of foul language, lack of respect for teachers, truancy, lying, tardiness, smoking, use of cell phones during class, and bullying. One of the efforts made to overcome these problems is through the habit of religious activities at school. This study aims to identify the forms of moral degradation among Generation Z students, the implementation of religious activities, as well as the challenges and solutions in their implementation. The research method used is qualitative with a descriptive design. Data collection techniques included observation, interviews, and documentation, while data validity was tested through extended observation and triangulation. Data analysis was conducted through data condensation, data presentation, and conclusion drawing. The results of the study indicate that religious activities such as dhuha prayers, group prayers, Quran recitation, and Islamic studies that are carried out routinely and structurally have proven to be effective in character building, improving discipline, and overcoming the moral degradation of Generation Z students